Evolution, Contemporary Dynamics, and Societal Impact of the Pharmaceutical Industry: Global Trends and the Moroccan Context (International Journal of Scientific Research and Management (IJSRM), 2025)
The pharmaceutical industry has undergone a remarkable transformation, evolving from artisanal apothecaries in the 19th century to a globalized and technologically advanced sector in the 21st century. This article examines the historical evolution of the industry, highlighting key scientific and technological advances, including genomics, artificial intelligence, and biofabrication, which have reshaped drug discovery, development, manufacturing, and commercialization. It also analyzes the strategic adaptation of pharmaceutical companies through diversification, specialization, generics, biologics, and digital health investments. The contemporary pharmaceutical landscape, particularly in emerging markets such as Morocco, is explored, emphasizing the influence of global dynamics, regulatory frameworks, and economic pressures. Finally, the societal, ethical, and economic impacts of the industry—including access to medicines, innovation, and policy influence—are discussed to provide a holistic understanding of its role in global health and the economy.